Translation, Adaptation, and Validation of the Malay Version of the Cardiac Rehabilitation Barriers Scale - Chai, Li Sze; Sidiah, John Siop; Zabidah, Putit; Lily, Lim; Azylina, Gunggu; Tie, Suk Fong (Taiwan Nurses Association, 2019)
Background: The rate of cardiac rehabilitation attendance at the Sarawak Heart Centre was identified as very low, and the reason has not been investigated. A scale is needed to identify barriers to participation in cardiac rehabilitation among patients with heart disease in Sarawak, Malaysia. Purpose: The purposes of this study were to translate, adapt, and evaluate the Malay-language version of the Cardiac Rehabilitation Barriers Scale (CRBS) and to measure the psychometric properties of the Malay-version CRBS to justify its use in Sarawak. Methods: A forward and back-translation method was used. Content validity was assessed by three experts. Psychometric testing was conducted on a sample of 283 patients who were eligible to participate in cardiac rehabilitation. A construct validity test was performed using factor analysis. Cronbach's alpha was used to examine the internal consistency. The test–retest reliability was calculated using the intraclass correlation coefficient on 22 participants. Independent-samples t test and analysis of variance were conducted to assess the criterion validity. Mean scores for total barriers of the scale and each individual factor were compared among the different patient characteristics.